Synthesis of manganese nanoparticles of Oolong tea extract by sonication method for a natural oral contrast media on magnetic resonance cholangiopancreatography - Fatimah, Fatimah; Susilaningsih, Neni; Sukmaningtyas, Hermina; Subagio, Agus (Gaceta Médica de Caracas, 2022)
Introduction: Magnetic resonance cholangio-pancreatography examination using natural contrast media has not provided an optimal image of gastroduodenal suppression that covers the image of the biliary system. Natural materials used as contrast media continue to be developed with various previous studies, but not many have been associated with using, nanoparticles as natural contrast media materials. This study aims to make manganese nanoparticles in oolong tea extract is used as an oral contrast medium.